PENGARUH SERTIFIKASI GURU TERHADAP PROFESIONALISME, PENGEMBANGAN DIRIBERKELANJUTAN DAN KEPUASAN KINERJA GURU IPS MAN Se Kota MALANG PASCASERTIFIKASI - Zuhroh, Niâ€™matuz (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
This study aims to determine the effect of Teacher Certification on Professionalism, Sustainable Self Development, and Job Satisfaction Teachers IPS MAN Malang Post- Certification. This study uses a quantitative approach and data taken by means of cross- section data collected at the same time from many subjects and retrieval of this data is only done once. In this research the data collection method used is by using questionnaire (questionnaire) that is given to all teachers IPS MAN Se Malang city that has been certified. Primary data taken are data about teacher professionalism, ongoing self-development and job satisfaction. While the questionnaire about teacher performance is filled by the Principal. Other secondary data is the number of teachers who have certification / teacher identity already certified. Measurement scale for primary data by using Likert Scale. Testing dataÂ  used validity and reliability test. The result of this research is that Teacher Certification to Professionalism, Self Development and Work Satisfaction of Teacher IPS MAN Malang Post Certification ". Influence significantly.Keywords: Teacher Certification, Professionalism, Self-sustained Development and Performance Satisfaction